Unveiling the growth mode and structure relaxation of Polytetrafluoroethylene film by radio-frequency magnetron sputtering. (1st October 2022) - Ma, Yi; Wu, Yifan; Yu, Yueling; Song, Yuxuan; Lu, Congda
Abstract: Relying on radio-frequency (RF) magnetron sputtering, Polytetrafluoroethylene (PTFE) films with a series of thicknesses in the range from 80 to 2000 nm were prepared on silicon substrates. The surface morphology and roughness of the PTFE films were measured by atomic force microscope (AFM) technology at microscale. Results indicated that the PTFE film grew in an island pattern during sputtering, while the surface roughness of PTFE films was almost invariable throughout the sputtering process. Then the structure relaxation of PTFE film annealed at 100 °C for 15–480 min was investigated. Annealing treatment induced columnar protrusions on the PTFE surface, which was due to the flow and rearrangement of molecules. During annealing duration, the columnar structures could continuously rearrange and decompose, and therefore lowering film thickness from 2000 to 1110 nm with increasing annealing time. Due to molecule flow and redistribution of the annealed film, the columnar structures were formed on the surface, which resulted in the higher roughness. Finally, the effects of film thickness and annealing time on the hydrophobicity were also studied.